Respuesta :

Answer: Fx+3F

Step-by-step explanation: you just use distributive property and multiply (f•x)+(F•3)

Answer: 2x - 1

Step-by-step explanation:

Given;

F(x) = 2x + 5........... *

we are to find F(x + 3 )

The first thing we will do is to equate x and x + 3  but it is clear that x in not equal to x + 3 , so we will write it as :

x = y + 3 and then make y the subject of the formula:

x = y + 3, that is

y = x - 3

This means that y(x) = f(x-3)

substitute x - 3 for x in the original expression given , that is

F(x+3) = 2 ( x - 3 ) + 5

F( x +3 ) = 2x - 6 + 5

F(x + 3) = 2x - 1